Origin of distorted 1T-phase ReS2: first-principles study. (19th February 2018) - Choi, Ji-Hae; Jhi, Seung-Hoon
Abstract: Group-VIIB transition metal dichalcogenides (TMDCs) are known to be stabilized solely in a distorted 1 T phase termed as 1 T″ phase, which is compared to many stable or metastable phases in other TMDCs. Using first-principles calculations, we study the structural origin of 1 T″ phase group-VIIB TMDCs. We find that quasi 1D Peierls-like instability is responsible for the transition to the 1 T″ phase ReS2 monolayer from the 1 T ′ phase, another distorted 1 T phase. Two half-filled bands in 1 T ′-ReS2 make sharp peaks in the Lindhard function that prompt the charge density wave (CDW) phase with large band gap opening. Our calculations show that overlapping of the two bands in a broad energy range leads to robust CDW phase or stable 1 T″ phase in group-VIIB TMDCs against compositional variation, which is in stark contrast to typical Peierls instability driven by a single band. Calculated total energy curve near the critical point exhibits the feature of the first-order Landau transition due to local chemical bonding. The structural stability of the 1 T″ phase in group-VIIB TMDCs is thus guaranteed by two half-filled bands and local chemical bonding.